Математичне моделювання систем електронної оптики з урахуванням симетрії граничних поверхонь - Мочурад, Леся Ігорівна (Національний університет "Львівська політехніка", 2018)
У дисертаційній роботі розв’язано актуальне наукове завдання розвитку математичних моделей та розробки нових методів розрахунку електростатичних полів класів електронно-оптичних систем з граничними поверхнями електродів, які володіють абелевою групою симетрії скінченного порядку. Цю задачу розв’язано шляхом розроблення та вдосконалення системи методів чисельного моделювання складних електростатичних полів. В основі цієї системи лежить метод інтегральних рівнянь у поєднанні з апаратом теорії груп, методом декомпозиції областей та апаратом функцій Гріна. Розроблена система методів дала можливість, по-перше, ефективніше використовувати оперативну пам’ять комп’ютера, зменшуючи її обсяг у квадрат порядку групи при формуванні кожної системи лінійних алгебричних рівнянь, які апроксимують відповідні інтегральні рівняння. По-друге, система методів дала можливість розпаралелити процес розв’язування задачі в цілому. В диссертационной работе решено актуальное научное задание развития математических моделей и разработки новых методов расчета электростатических полей классов электронно-оптических систем с предельными поверхностями электродов, которые обладают абелевой группой симметрии конечного порядка. Эту задачу решено путем разработки и совершенствования системы методов численного моделирования сложных электростатических полей. В основе этой системы лежит метод интегральных уравнений в сочетании с аппаратом теории групп, методом декомпозиции областей и аппаратом функций Грина. Предложенная система методов позволила, во-первых, эффективно использовать оперативную память компьютера, уменьшая ее объем в квадрат порядка группы при формировании каждой системы линейных алгебраических уравнений, аппроксимирующих соответствующие интегральные уравнения. Во-вторых, система методов дала возможность распараллелить процесс решения задачи в целом. The modern scientific task of the electrostatic field calculations in the modeling process of the electron-optical systems with the symmetry appeared in geometry of the surfaces- electrodes is solved in the thesis. This solution is realized via the construction and improvement of the numerical modeling methods in the case of the complicated electrostatic fields. These methods are based on the integral equations method connected with the group theory, domain decomposition method and apparatus of Green function. The proposed system of methods allowed us to use the main computer memory more effectively, diminishing it by squared order of group while constructing every system of linear algebraic equations which approximate the corresponding integral equations. Thus, the type of tasks which assumes a numeral modelling with the use of the method of boundary integral equations is broaden. Also, preconditions for parallelization of the solving process in general are created. Taking into account the specificity of the open-circuit surfaces it is possible to decrease the amount of the controlled special points considerably, and also substantially to simplify the algorithm of calculations. The procedure of parallelization was realized via the most popular means of OpenMP. With the aim to take into account the singular behaviour of the solution in the circuit of the open surface a posteriori method of the error evaluation is created. It is also noticed that under predominance of one geometrical component surface over the other ones the changes of the potential value in its transversal cuts close to central are not noticeable. To state the highquality representation of the field in the central transversal cuts of the electron-optical systems, one can limit the research by the flat cuts of spatial constructions, since boundary surfaces satisfy the geometrical properties mentioned above. Taking into account the specific characters of initial boundary value problem in the mathematical model, describing socalled flat electrostatic field, is considered. Thereby the main accent is made on the equivalence of last one to the integral first-order equation and the problem of additive constant calculation. This constant appears in the integral representation of flat electrostatic field. There is stated that the constant mentioned above is easily calculated in the presence of symmetry disposition of boundary surface constituents. The proposed concept is illustrated by the numerical solving of some model tasks. There are obtained the approximate solutions of some spatial problems with different configurations of surfaces-electrodes and different boundary values of potentials using the socalled flat approximation. Such type problems arise in the mathematical modelling of electronic optical systems. The advantages of the proposed methods were demonstrated while solving them. To prove the reasonability and estimation of the technique efficiency a few numerical experiments were carried out. The equipotential lines are used for the representation of the electrostatic field.
Математическое моделирование систем электронной оптики с учетом симметрии граничных поверхностей
Mathematical modelling of the electronic optic systems taking into account the symmetry of the boundary surfaces
Keywords: математичне моделювання; електронно-оптична система; метод інтегральних рівнянь; абелева група симетрії; функція Гріна; декомпозиція складних областей; математическое моделирование; электронно-оптическия система; метод интегральных уравнений; абелева группа симметрии; функция Грина; декомпозиция сложных областей; mathematical modelling; electronic optical system; integral equation method; Abelian symmetry group; Green function; domain decomposition; 537.2+519.632+681.7